Local communities’ and indigenous peoples’ land and forestry rights: Assessing the law and practice on tenure security in Kenya - Kibugi, R. (Center for International Forestry Research, 2021)
This study aimed to understand whether, and to what extent, Kenyan legal provisions are sufficient to secure community land rights, particularly those of indigenous peoples and local communities. It assesses the adequacy of Kenya’s legal framework for protecting and promoting tenure rights of forest communities, including over protected areas. There is an enduring problem pertaining to historical land injustices, where certain indigenous peoples and local communities have sought formal recognition of their land rights over areas classified as public land, which are managed mainly as public forests or national wildlife reserves